Materiales reciclables con objetos creativos inciden en el aprendizaje significativo de los estudiantes de bachillerato del Colegio Fiscal Simón Bolívar, cantón Guayaquil, provincia del Guayas - Espinoza Criollo, Yomayra del Roció (2018)
The culture of recycling is a learning that within society has gradually developed; it is within the educational Institutions in which this learning must be potentiated, developing not only the collection but also the selection of material that can be reused to elaborate craft objects. Teachers should encourage students to practice creative activities, with them motivating them to various academic learnings as an artisanal educational experience to develop skills and abilities, keep them active to edit leisure or boredom within the classroom, economize and facilitate parents of family. The elaboration of the artisanal objects with recyclable material offers the students practical experience in which they are involved when handling materials of easy acquisition, that in the journey they discover skills that they did not know, and they verify that the used or recycled materials can be made creative adornments, and contribute to the care of nature. The general objective of this project is to design a proposal for the creation of a physical space where students can offer creative objects for the students based on recyclable material, developing in the students of the Fiscal School "SIMÓN BOLÍVAR" Provinces of Guayas , Guayaquil Canton.